Pengaruh Kualitas E-Banking Dan Kualitas Layanan Terhadap Kepuasan Nasabah - Ardhieva Wiraldhy Ruslanie; Filani Zikri Hassan; Marwan Effendy (Jurnal Informatika Kesatuan, 2022)
To determine the effect of e-banking and service quality on satisfaction at PT. Bank Mandiri Bogor City Branch. The analytical method used in this study is multiple linear regression with customer loyalty being the dependent variable and two independent variables, namely e-banking and service quality. Results Processing data obtained by the LN = Y model: 0.166 + 0.453X1 + 0.527X2 In the regression coefficient, KP produces every e-banking increase of 0.453, one unit is predicted, will get a profit, amounting to 0.166 units and can also be changed. The coefficient of determination (R1) is 0.888, this shows e-banking variables and service quality contribute or contribute as much as 88% to the variable satisfaction satisfaction at PT. Bank Mandiri Bogor City Branch. Partially, the test results showed each e-banking variable and service quality were significant to investment loyalty at PT. Bank Mandiri Bogor City Branch so the hypothesis is accepted. Simultaneously, the results of the F test indicate that together e-banking variables and related service quality are significant to investment loyalty at PT. Bank Mandiri Bogor City Branch so the hypothesis is accepted. Keywords: E-Banking, Service Quality, Customer Loyalty